THE TRANSMISSION OF NERVE IMPULSES AT NEUROEFFECTOR JUNCTIONS AND PERIPHERAL SYNAPSES - ROSENBLUETH, ARTURO; GOMEZ, GABRIEL (Hospital Spanish, CD MEXICO, DF, MEX, 1950)
Scaphiopus couchii, Bufo cristatus, and Microhyla olivacea are recorded; the latter two are additions to the fauna of the State The 2d is reported also from Nautla, Veracruz A list of the amphibian
Keywords: TRANSMISSION, NERVE IMPULSES, NEUROEFFEC TOR JUNCTIONS, PERIPHERAL SYNAPSES; MULTIDISCIPLINARIA; MEDICINA INTERNA; NEUROLOGIA